Analysis of the Effectiveness of Primary School Administrative Management in Supporting the Learning Process (IJORER : International Journal of Recent Educational Research, 2026)
Administrative management in primary schools is often viewed as a technical support system; however, its effectiveness plays a crucial indirect role in shaping learning conditions. This study aims to reconceptualize administrative management effectiveness by examining the processes through which administrative practices support the learning process in primary schools. Employing a qualitative case study approach, this research was conducted in three public primary schools in South Tapanuli, North Sumatra. Data were collected through observations, in-depth interviews, and documentation, and analyzed using thematic and process-oriented analysis. The findings reveal that administrative effectiveness is not determined solely by formal structures or digital adoption, but emerges through interconnected processes, including the redistribution of teachers’ administrative workload, coordination efficiency, and information accuracy. Principal leadership functions as a mediating mechanism that shapes administrative coordination and work culture, while digitalization operates as a conditional accelerator whose impact depends on human resource readiness. Based on these findings, this study proposes a process-based conceptual model explaining how administrative management indirectly supports classroom learning. This research contributes to the literature by shifting the discussion of school administrative effectiveness from outcome-based evaluation to a process-oriented perspective and offers empirical insights for strengthening administrative governance in primary education.